The power of metaphor in thesis writing process - Hanić Jasmina; Pavlović Tanja; Jašić Alma Jahić (ExELL (Explorations in English Language and Linguistics), 2023)
The article contributes to the discussion of writing at the master’s level by investigating metaphors underlying the process of writing a master’s thesis from the perspective of graduate students. The analysis focuses on the use of metaphors in semi-structured interviews conducted with graduate students who defended their thesis and reflected on the whole process. Their metaphor use is non-elicited and this rhetorical device is spontaneously used showing that thesis writers conceptualize their research and all it entails in metaphorical terms to a significant extent. Despite the fact that thesis writers themselves were not encouraged to pay attention to or use metaphorical language, their narratives reveal the interplay of metaphors when describing the writing process.